Mechanism and efficiency of photocatalytic triclosan degradation by TiO2/BiFeO3 nanomaterials - Gen Liu; Yingzi Lin; Siwen Li; Chunyan Shi; Daihua Zhang (Water Science and Technology, 2022)
Hierarchical porous TiO2 photocatalytic nanomaterials were fabricated by impregnation and calcination using a peanut shell biotemplate, and TiO2/BiFeO3 composite nanomaterials with different doping amounts were fabricated using hydrothermal synthesis. The micromorphology, structure, element composition and valence state of the photocatalyst were analyzed using a series of characterization methods, including X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), BET surface area (BET), X-ray photoelectron spectroscopy (XPS), UV-visible diffuse reflectance (UV-vis), fluorescence spectroscopy (PL) and other technological means. Finally, the degradation mechanism and efficiency of BiFeO3 composite photocatalyst on the target pollutant triclosan were analyzed using a xenon lamp to simulate sunlight. The results showed that TiO2/BiFeO3 catalyst fabricated using a peanut shell biotemplate has a specific surface area of 153.64 m2/g, a band gap of 1.92 eV, and forms heterostructures. The optimum doping amount of TiO2/BiFeO3 catalyst was 1 mol/mol, and the degradation rate was 81.2%. The main active substances degraded were ·O2−and ·OH. The degradation process measured is consistent with the pseudo-first-order kinetic model. HIGHLIGHTS TiO2 loading can increase the specific surface area and empty volume of BiFeO3 and provide more active sites.; Through total organic carbon analysis, the mineralization rate of total organic carbon of TiO2/BiFeO3 photocatalyst is 58.9%.; h+ and ·OH are the active substances for degradation of triclosan. Relatively speaking, · OH has more obvious inhibition on triclosan and is the main active oxidizing substance.;